Zakaj v Sloveniji še ni dovolj inoviranja - gospodarsko in kulturno razvojni razlogi - Mulej, Matjaž (Naše gospodarstvo, 2006)
The European Union found Slovenia innovative enough to accept it as a member. The basis for its assessment might have been the institutional order rather than the actual culture and practice that cause institutions to function poorly. Insight into economic and cultural development shows that one must take a thorough look into the given roots of culture and innovate the culture. We suggest a few measures that might perhaps bring the institutional structure and the given culture closer to each other and help us innovate them rather than technology only.
Keywords: management; Slovenia; Slovenija; podjetja; razvojna strategija; inovacije; inoviranje